Peran Masyarakat Bandungrejo dalam Pembentukan Jiwa Wirausaha Anak Sekolah Dasar - Kharis, Baihaqi Al; Purbasari, Imaniar; Fajrie, Nur (Peneliti.net, 2024)
This study aims to determine the role of the family in forming an entrepreneurial spirit in elementary school-aged children in Bandungrejo Village. To find out the role of the community in forming an entrepreneurial spirit in elementary school age children in Bandungrejo Village. This study uses a type of qualitative research with research subjects namely parents and students. Data collection techniques include the stages of observation, interviews and documentation. Data analysis includes data reduction, data presentation, verification or conclusion. The results showed that the role of the family in forming an entrepreneurial spirit in elementary school-age children in Bandungrejo Village included fostering self-confidence, teaching task- and result-oriented children, teaching children to take risks, accustoming children to leadership, accustoming children to having a self-oriented spirit. future. The role of the community in shaping the entrepreneurial spirit of elementary school-age children in Bandungrejo Village includes involvement in making decisions to advance entrepreneurship in Bandungrejo Village, forms of community contribution to increase the role of children in entrepreneurship, work organization to regulate business development and setting goals for entrepreneurial development in Bandungrejo Village.